Pelleting and heat treatment of fattening lamb rations - Menzies, C.S.; Cox, R.F.; Deyoe, C.W.; Pfost, H.B. (Kansas Agricultural Experiment Station, 2011)
This test is a follow-up of the study reported on page 5 concerning the effects of form and heat treatment of rations on lamb feedlot performance.
Keywords: Sheep; Pelleting; Performance; Feedlot